Impact of NOTAM on security and efficiency performance of flights (overview) - A. V. Prokhorov (Научный вестник МГТУ ГА)
The purpose of this work is to analyze and assess the impact of NOTAM on the flight safety and efficiency. The main problems associated with NOTAM were considered: number of NOTAMs, the practical use of NOTAM information, technical limitations of the current NOTAM system. Examples of the negative impact of NOTAM on the quality of air navigation support, safety and efficiency of flights are presented. Also, the best practice of solving problems, related to NOTAM in the world, is presented with using: Q-code and flight planning systems (on the example of Lido Flight 4D). The concept of the European AIS Database (EAD), developed on the basis of the Aeronautical Information Exchange Model (AIXM), is presented. The concept of Digital NOTAM, implemented on the basis of AIXM and intended for the exchange, automatic processing and interpretation of the dynamic aeronautical data, is considered. The research studies the new modernized NOTAM system – Federal NOTAM System (FNS – Federal NOTAM System), developed by the Federal Aviation Administration (FAA) of the United States, which allows encoding the Digital NOTAM. ICAO's plans for the transition from the concept of Aeronautical Information Service (AIS) to the Aeronautical Information Management (AIM), applying the principles of the System Wide Information Management (SWIM) concept, were analyzed. As a result of the analysis of the current NOTAM system and the modernized NOTAM system (FNS from FAA), conclusions were drawn that the implementation of Digital NOTAM should solve the technical part of the problems associated with NOTAM, brought about by the use of modern communications (internet) and new data exchange standards (AIXM), which, as a result, will lead to an increase in the level of safety and efficiency of flights. At the same time, problems with NOTAM caused by human factors remain unresolved, due to incorrect use of the NOTAM instrument.